Effects of a 12-Week Interventional Exercise Programme on Muscle Strength, Mobility and Fitness in Patients With Diabetic Foot in Remission: Results From BIONEDIAN Randomised Controlled Trial - Vrátná, Eliška; Husáková, Jitka; Jarošíková, Radka; Dubský, Michal; Wosková, Veronika; Bém, Robert; Jirkovská, Alexandra; Králová, Kateřina; Pyšková, Bára; Lánská, Věra; Fejfarová, Vladimíra (Frontiers in Endocrinology, 2022)
Objectives: Diabetic foot syndrome (DFS) is a serious late diabetic complication characterised by limited joint mobility and other biomechanical and muscle abnormalities. Aim: To evaluate the effect of an interventional exercise programme on anthropometric parameters, muscle strength, mobility and fitness in patients with diabetic foot in remission. Data Sources and study selection: Thirty-eight patients with type 2 diabetes and DFS without active lesions (mean age 65±6.9 years, BMI 32±4.7 kg.m-2, waist-hip ratio (WHR)1.02 ± 0.06) were enrolled in our randomised controlled trial. All subjects were randomised into two groups: an intervention group (I; n=19) and a control group (C; n=19). The 12-week exercise intervention focused on ankle and small-joint mobility in the foot, strengthening and stretching of the lower extremity muscles, and improvements in fitness. Changes (∆=final minus initial results) in physical activity were assessed using the International Physical Activity Questionnaire (IPAQ), with joint mobility detected by goniometry, muscle strength by dynamometry, and fitness using the Senior Fitness Test (SFT). Data extraction: Due to reulceration, 15.8% of patients from group I (3/19) and 15.8% of patients from group C were excluded. Based on the IPAQ, group I was more active when it came to heavy (p=0.03) and moderate physical activity (p=0.06) after intervention compared to group C. Group I improved significantly in larger-joint flexibility (p=0.012) compared to controls. In group I, dynamometric parameters increased significantly in both lower limbs (left leg; p=0.013, right leg; p=0.043) compared to group C. We observed a positive trend in the improvement of fitness in group I compared to group C. We also confirmed positive correlations between heavy physical activity and selected parameters of flexibility (r=0.47; p=0.007), SFT (r=0.453; p=0.011) and dynamometry (r=0.58; p<0.0025). Anthropometric parameters, such as BMI and WHR, were not significantly influenced by the intervention programme. Conclusion: Our 12-week interventional exercise programme proved relatively safe, resulting in improved body flexibility and increased muscle strength in DF patients in remission.